Positive electrode active material and preparation method thereof, positive electrode plate and sodium ion battery

By designing the particle structure and element doping of the core and the coating layer, the chemical composition of the positive electrode active material is optimized, and the problems of structural instability and poor circulation performance of the existing positive electrode active material at high voltage are solved, achieving high energy density and stable battery performance.

CN119812270AActive Publication Date: 2025-04-11BEIJING EASPRING MATERIAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411999035.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing positive electrode active materials have unstable structures under high voltages, prone to rupture, poor circulation performance, and difficult to meet the application of sodium ion batteries in the field of high energy density.

Method used

By designing the particle structure of the core and the coating layer, the average particle size of the particles in the core is smaller and the length diameter is relatively large, and the average particle size of the particles in the coating layer is larger and the length diameter is relatively small. Combined with the doping of different elements, the chemical composition of the positive electrode active material is optimized.

Benefits of technology

The positive electrode active material has excellent capacity and structural stability under high voltage, overcomes the problems of structural instability and poor circulation performance, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812270A_ABST
    Figure CN119812270A_ABST
Patent Text Reader

Abstract

The invention discloses a positive active material and a preparation method thereof, a positive pole piece and a sodium ion battery. The positive electrode active material comprises an inner core, the length-diameter ratio of primary particles in the inner core is L1, and the average particle size of the primary particles in the inner core is D1; the coating layer is located on at least part of the surface of the inner core, the length-diameter ratio of primary particles in the coating layer is L2, the average particle size of the primary particles in the coating layer is D2, L1 / L2 is larger than 1, and D2 / D1 is larger than 1. The average particle size of the primary particles in the inner core is small and the length diameter of the primary particles in the inner core is large, and the average particle size of the primary particles in the coating layer is large and the length diameter of the primary particles in the coating layer is small, so that the primary particles in the inner core can well exert the self capacity, and the primary particles in the coating layer can effectively improve the structural stability; therefore, the positive electrode active material has relatively excellent capacity exertion and relatively high structural stability in the charge-discharge cycle process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sodium electricity, and specifically, to positive electrode active materials and preparation methods thereof, positive electrode sheets, and sodium ion batteries. Background Art

[0002] In recent years, with the continuous progress of new energy technology and the concept of sustainable energy being deeply rooted in people's hearts, the new energy industry represented by lithium-ion batteries has achieved unprecedented rapid development. Lithium-ion batteries can be seen in the fields of energy storage, power batteries, 3C digital products, etc., which have a profound impact on all aspects of our daily life. However, the lithium used in lithium-ion batteries is expensive and fluctuates greatly. In addition, my country's lithium ore resources are scarce, and its external dependence is as high as 80%. Therefore, it is necessary to develop new electrochemical systems. Sodium-ion batteries have attracted the attention of many researchers because of their abundant sodium resources and low cost. Among the positive active materials of sodium-ion batteries, layered metal oxides have become the most likely materials to meet the requirements of power batteries because of their high gram capacity and similar production process to lithium-ion battery ternary materials. However, there are still many problems in the actual production and application of current positive active materials that need to be further improved. Summary of the invention

[0003] In the first aspect of the present application, the present application proposes a positive electrode active material, comprising: a core, wherein the aspect ratio of primary particles in the core is L1, and the average particle size of primary particles in the core is D1; ​​and a coating layer, wherein the coating layer is located on at least part of the surface of the core, wherein the aspect ratio of primary particles in the coating layer is L2, and the average particle size of primary particles in the coating layer is D2, L1 / L2>1, D2 / D1>1. The average particle size of primary particles in the core is small and the aspect ratio is large, while the average particle size of primary particles in the coating layer is large and the aspect ratio is small, thereby the primary particles in the core can better exert their own capacity, and the primary particles in the coating layer can effectively improve the structural stability, so that the positive electrode active material has both better capacity exertion and higher structural stability during the charge and discharge cycle.

[0004] In some embodiments, 1.5≤L1 / L2≤4.2. Thus, the primary particles in the core can provide a relatively excellent ion transmission channel, which is beneficial to the capacity of the positive electrode active material, and the primary particles in the coating layer are close to single crystal particles, which can improve the structural stability of the positive electrode active material.

[0005] In some embodiments, L1 is 3 to 5. Thus, the ionic conductivity of the primary particles in the inner core is relatively high.

[0006] In some embodiments, L2 is 1 to 3. Thus, the structural stability of the primary particles in the coating layer is better.

[0007] In some embodiments, 3≤D2 / D1≤13; alternatively, 4≤D2 / D1≤10. Thus, the positive electrode active material has excellent structural stability.

[0008] In some embodiments, D1 is 0.08 μm-0.3 μm. Thus, the specific surface area of ​​the primary particles in the core is larger, and the capacity is better.

[0009] In some embodiments, D2 is 0.6 μm-1.5 μm. Thus, the structural stability of the primary particles in the coating layer is high.

[0010] In some embodiments, the porosity of the inner core is Q1, the porosity of the coating layer is Q2, and Q1 / Q2>1.

[0011] In some embodiments, 2≤Q1 / Q2≤7; alternatively, 2≤Q1 / Q2≤5. Thus, the positive electrode active material has both better capacity performance and higher structural stability.

[0012] In some embodiments, 4%≤Q1≤8%. Thus, the primary particles in the inner core can be fully infiltrated with the electrolyte to improve the capacity.

[0013] In some embodiments, 1%≤Q2≤2.5%. Thus, the contact area between the primary particles and the electrolyte in the coating layer is relatively low, which can effectively improve the structural stability of the positive electrode active material.

[0014] In some embodiments, the radius of the positive electrode active material is R, 3 μm≤R≤7 μm. Thus, the capacity and structural stability of the positive electrode active material are both excellent.

[0015] In some embodiments, the coating layer has a thickness of 0-0.4R, optionally, 0-0.35R. Thus, the coating layer can effectively improve the structural stability of the positive electrode active material and has little effect on the capacity of the positive electrode active material.

[0016] In some embodiments, the positive electrode active material satisfies the chemical formula: Na a (Ni 1-b-c-d Fe b Mn c M d )N e O 2-f, wherein M includes at least one of V, Ta, La, Al, Ce, Y, Ba, Zr, Ca, W, Nb, Si, Mo, F, P, and Ti, N includes at least one of Cu, Cr, Mg, Sr, Fe, Ni, Mn, Sn, Zn, B, and Co, 0.95≤a≤1.15, 0<b≤0.50, 0<c≤0.70, 0<d≤0.15, 0<e≤0.15, and f satisfies one of the following conditions: when both M and N are cations, f=0; when both M and N are anions, f=d+e; when M is an anion and N is a cation, f=d; when N is an anion and M is a cation, f=e. Thus, by doping with different elements, a positive electrode active material that meets different performance requirements can be obtained.

[0017] In the second aspect of the present application, the present application proposes a method for preparing the aforementioned positive electrode active material, comprising: mixing a nickel source, an iron source, a manganese source, a chelating agent, and a precipitating agent to obtain a precursor slurry, and performing a drying treatment to obtain a precursor material; mixing the precursor material, a sodium source, and an M source, and performing a first sintering treatment to obtain a positive electrode active material intermediate, wherein the temperature of the first sintering treatment is T1; mixing the positive electrode active material intermediate with an N source, and performing a second sintering treatment to obtain a positive electrode active material, wherein the temperature of the second sintering treatment is T2, T1<T2. Thus, the growth process of the primary particles in the core and the coating layer of the positive electrode active material can be precisely controlled, so that the average particle size of the primary particles in the core is smaller and the aspect ratio is larger, and the average particle size of the primary particles in the coating layer is larger and the aspect ratio is smaller.

[0018] In some embodiments, T2-T1<200° C.; optionally, 10° C.<T2-T1<120° C. This helps to promote the growth and fusion of primary particles in the coating layer during the second sintering process, and has little effect on the primary particles in the core.

[0019] In some embodiments, T1 is 800° C.-960° C., and the holding time of the first sintering treatment is 10 h-15 h. This helps to form primary particles with a smaller average particle size and a larger aspect ratio in the inner core.

[0020] In some embodiments, T2 is 850° C.-1000° C., and the second sintering treatment is performed at a holding time of 8 h-10 h. This helps to form primary particles with a larger average particle size and a smaller aspect ratio in the coating layer.

[0021] In some embodiments, the nickel source, iron source, and manganese source independently include at least one of sulfate, chloride, and acetate of the corresponding element; and / or the complexing agent includes at least one of ammonia water, sodium oxalate, sodium citrate, and ethylenediaminetetraacetic acid; and / or the precipitating agent includes at least one of sodium hydroxide and sodium carbonate. Thus, the raw material source is abundant, the environmental pollution is small, and it is helpful to reduce the manufacturing cost.

[0022] In some embodiments, the sodium source includes at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium sulfate, sodium chloride, sodium fluoride, and sodium sulfide; and / or, the M source includes at least one of sulfate, carbonate, oxalate, phosphate, nitrate, and chloride corresponding to the M element; and / or, the N source includes at least one of oxide, sulfide, hydroxide, oxyacid, carbonate, oxalate, phosphide, and oxyhydroxyl corresponding to the N element. Thus, the raw material source is abundant, the environmental pollution is small, and it is helpful to reduce the manufacturing cost.

[0023] In the third aspect of the present application, the present application proposes a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises the aforementioned positive electrode active material or the positive electrode active material prepared by the aforementioned method. Therefore, the positive electrode sheet has all the features and advantages of the aforementioned positive electrode active material and its preparation method, which will not be described in detail here.

[0024] In a fourth aspect of the present application, the present application proposes a sodium ion battery, comprising the aforementioned positive electrode sheet. Thus, the sodium ion battery has all the features and advantages of the aforementioned positive electrode sheet, which will not be elaborated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0026] Figure 1 This is a scanning electron microscope image of the positive electrode active material of Example 1 of the present application.

[0027] Figure 2 This is a scanning electron microscope image of a cross section of the positive electrode active material of Example 1 of the present application.

[0028] Figure 3 This is a scanning electron microscope image of the positive electrode active material of Comparative Example 1 of the present application.

[0029] Figure 4 This is a scanning electron microscope image of the cross section of the positive electrode active material of Comparative Example 1 of the present application.

[0030] Description of reference numerals:

[0031] Core 10; cladding layer 20. DETAILED DESCRIPTION

[0032] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0033] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0034] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0035] In the description of this application, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. The value of each number may differ by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.

[0036] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0037] In the description of the present application, it should be understood that the terms "thickness", "radial", "inner", "outer", etc., indicating the orientation or positional relationship are based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the referred structure must have a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0038] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.

[0039] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.

[0040] In the present application, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0041] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0042] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0043] In order to give full play to the capacity of the positive electrode active material and meet the demand for high energy density as much as possible. Sodium ion batteries need to be used for charge and discharge cycles at a higher upper limit voltage, but the stability of the positive electrode active material is generally poor at high voltage. The positive electrode active material in the related art is generally a secondary particle formed by the accumulation of primary particles with the same particle size, and the primary particles located on the surface and inside of the secondary particles have no significant difference in particle size, aspect ratio, etc. When the particle size of the primary particles forming the secondary particles is relatively small, the specific surface area of ​​the positive electrode active material is relatively large, the area in contact with the electrolyte is relatively large, the transmission path of the sodium ions is relatively short, and a higher capacity release is exhibited under the same charge and discharge conditions. However, a larger specific surface area increases the area where side reactions occur between the positive electrode active material and the electrolyte, causing the cycle performance of the positive electrode active material to deteriorate at high voltage. When the particle size of the primary particles forming the secondary particles is relatively large, the specific surface area of ​​the positive electrode active material is relatively small, and the structural stability at high voltage can be improved, but it also causes the capacity of the positive electrode active material to deteriorate. That is, when the particle size of the primary particles in the positive electrode active material is large or small, it will seriously restrict the application of the positive electrode active material in the field of high energy density.

[0044] In the present application, the ion transmission path in the primary particles with a smaller average particle size and a larger aspect ratio in the core is shorter, and there are more ion transmission channels, which can effectively improve the capacity of the positive electrode active material. At the same time, the primary particles with a larger average particle size and a smaller aspect ratio in the coating layer are relatively close in size in all directions, have a structure similar to that of a single crystal material, have a higher structural stability and a small contact area with the electrolyte, which can effectively improve the stability of the primary particles in the core during the charge and discharge cycle. By combining a core with a smaller average particle size and a larger aspect ratio of primary particles with a coating layer with a larger average particle size and a smaller aspect ratio of primary particles, under the premise of meeting the high gram capacity requirements, the problems of structural instability, easy rupture of particles, and poor cycle performance of the positive electrode active material in the related art during high voltage cycles are effectively overcome.

[0045] In the first aspect of the present application, the present application proposes a positive electrode active material, referring to Figure 1 and Figure 2 , comprising: a core 10, wherein the aspect ratio of the primary particles in the core 10 is L1, and the average particle size of the primary particles in the core 10 is D1; ​​and a coating layer 20, wherein the coating layer 20 is located on at least part of the surface of the core 10, wherein the aspect ratio of the primary particles in the coating layer 20 is L2, and the average particle size of the primary particles in the coating layer 20 is D2, L1 / L2>1, D2 / D1>1. The average particle size of the primary particles in the core 10 is small and the aspect ratio is large, while the average particle size of the primary particles in the coating layer 20 is large and the aspect ratio is small, thereby the primary particles in the core 10 can exert their own capacity at a good level, and the primary particles in the coating layer 20 can effectively improve the structural stability, so that the positive electrode active material has both better capacity exertion and higher structural stability during the charge and discharge cycle.

[0046] As an example, refer to Figure 1 and Figure 2 The positive electrode active material can be a secondary spherical particle with a core-shell structure, wherein the core 10 is composed of primary particles with a smaller average particle size, and the coating layer 20 is formed by surrounding primary particles with a larger average particle size.

[0047] By counting the aspect ratios of all primary particles of a single positive electrode active material particle in the selected area and calculating the average value, the aspect ratio of the primary particles in the selected area can be obtained. As an example, the aspect ratio of the primary particles in the present application can be tested by the following method: using an ion milling device to cut the positive electrode active material to obtain the cross-sectional structure of the positive electrode active material; using a scanning electron microscope (such as Hitachi S-4800) to test the cross-sectional structure of the aforementioned positive electrode active material to obtain an electron microscope photograph. Subsequently, the particle aspect ratio analysis module in the lithium battery material intelligent image analysis system software (software vendor: Opotong (China) Co., Ltd., version number: Metis Vision1.8326) can be used to obtain it.

[0048] In the present application, the aspect ratio refers to the ratio of the maximum dimension of a primary particle in the length direction to its maximum dimension in the width direction, wherein the maximum dimension of the primary particle in the length direction is greater than its maximum dimension in the width direction, and the length direction of the primary particle is perpendicular to the width direction.

[0049] Average particle size D p It can be obtained by calculating the average value of the longest diagonal D1 and the shortest diagonal D2 of the primary particles in the selected range in the electron microscope photo, that is, n is the total number of primary particles in the selected area in the electron microscope photo. As an example, the average particle size of the primary particles in the present application can be obtained by testing in the following way: after obtaining the cross-sectional structure electron microscope photo of the positive electrode active material by scanning electron microscope, the particle size analysis module in the lithium battery material intelligent image analysis system software (software vendor: OPTON (China) Co., Ltd., version number: Metis Vision 1.8326) is used to obtain the average particle size of the primary particles in the present application.

[0050] In some embodiments, 1.5≤L1 / L2≤4.2.

[0051] As examples, L1 / L2 may be 1.5, 2, 2.5, 3, 3.5, 4 or 4.2.

[0052] When L1 / L2 is within the aforementioned range, the aspect ratio of the primary particles in the inner core is relatively large, which can provide a relatively excellent ion transport channel, and is beneficial to the capacity of the positive electrode active material.

[0053] In some embodiments, L1 is 3 to 5. Thus, the ionic conductivity of the primary particles in the inner core is relatively high.

[0054] As examples, L1 may be 3, 3.5, 4, 4.5, or 5.

[0055] When L1 is within the aforementioned range, the ion transmission path of sodium ions from the center of the primary particle to the surface is shorter and there are more transmission channels, which is conducive to the embedding and detachment of sodium ions during the charging and discharging process and improves the capacity of the core.

[0056] In some embodiments, L2 is 1 to 3. Thus, the structural stability of the primary particles in the coating layer is better.

[0057] As examples, L2 can be 1, 1.5, 2, 2.5, or 3.

[0058] During the charge and discharge process of the battery, the positive electrode active material will undergo volume changes. When L2 is within the aforementioned range, the sizes of the primary particles in the coating layer are relatively close in all directions, which can effectively alleviate the stress caused by the volume change of the positive electrode active material during the charge and discharge process, reduce the generation of cracks due to stress concentration, and thus improve the structural stability of the positive electrode active material during the charge and discharge process.

[0059] In some embodiments, 3≤D2 / D1≤13; alternatively, 4≤D2 / D1≤10. Thus, the positive electrode active material has excellent structural stability.

[0060] As examples, D2 / D1 can be 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or 13.

[0061] When D2 / D1 is within the aforementioned range, the average particle size of the primary particles in the coating layer is larger, and the primary particles in the coating layer are close to single crystal particles, which can improve the structural stability of the positive electrode active material.

[0062] In some embodiments, D1 is 0.08 μm-0.3 μm. Thus, the specific surface area of ​​the primary particles in the core is larger, and the capacity is better.

[0063] As an example, D1 may be 0.08 μm, 0.12 μm, 0.16 μm, 0.20 μm, 0.24 μm, 0.28 μm, or 0.3 μm.

[0064] When D1 is within the aforementioned range, the specific surface area of ​​the primary particles is relatively large, and more areas are in contact with the electrolyte, which facilitates the rapid transmission of sodium ions at the interface between the two phases.

[0065] In some embodiments, D2 is 0.6 μm-1.5 μm. Thus, the structural stability of the primary particles in the coating layer is high.

[0066] As an example, D2 may be 0.6 μm, 0.8 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, or 1.5 μm.

[0067] When D2 is within the aforementioned range, the specific surface area of ​​the primary particles is relatively small, and the surface area in contact with the electrolyte is correspondingly reduced, which helps to reduce the incidence of unnecessary interfacial side reactions and improve the structural stability of the positive electrode active material.

[0068] In some embodiments, the porosity of the inner core is Q1, the porosity of the coating layer is Q2, and Q1 / Q2>1.

[0069] When the porosity of the inner core is large, it is beneficial for the primary particles in the inner core to be fully infiltrated by the electrolyte, thereby improving the capacity utilization; when the porosity of the coating layer is small, it can effectively reduce the contact area between the outer surface of the positive electrode active material and the electrolyte, thereby improving the structural stability of the outer surface of the positive electrode active material.

[0070] The porosity of the selected area can be obtained by counting the ratio of the pore area between the primary particles of a single positive electrode active material particle in the selected area to the area of ​​the selected area. As an example, the porosity in this application can be tested by the following method: after obtaining a cross-sectional structure electron microscope photograph of the positive electrode active material by scanning electron microscope, the cross-sectional pore analysis module in the lithium battery material intelligent image analysis system software (software vendor: Oupotong (China) Co., Ltd., version number: Metis Vision1.8326) is used to obtain the porosity.

[0071] In some embodiments, 2≤Q1 / Q2≤7; alternatively, 2≤Q1 / Q2≤5. Thus, the positive electrode active material has both better capacity performance and higher structural stability.

[0072] As examples, Q1 / Q2 can be 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, or 7.

[0073] In some embodiments, 4%≤Q1≤8%. Thus, the primary particles in the inner core can be fully infiltrated with the electrolyte to improve the capacity.

[0074] As an example, Q1 may be 4%, 5%, 6%, 7%, or 8%.

[0075] In some embodiments, 1%≤Q2≤2.5%. Thus, the contact area between the primary particles and the electrolyte in the coating layer is relatively low, which can effectively improve the structural stability of the positive electrode active material.

[0076] As examples, Q2 may be 1%, 1.5%, 2%, or 2.5%.

[0077] In some embodiments, the radius of the positive electrode active material is R, 3 μm≤R≤7 μm. Thus, the capacity and structural stability of the positive electrode active material are both excellent.

[0078] As an example, R may be 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, or 7 μm.

[0079] When the radius of the positive electrode active material is within the aforementioned range, the radius of the positive electrode active material is moderate, the transmission path of the sodium ions is short, the positive electrode active material is in full contact with the electrolyte, and has fewer side reactions with the electrolyte, is less likely to have structural rupture under high voltage, and has better cycle performance.

[0080] It should be noted that the radius of the positive electrode active material is the average value of the sum of the maximum distance from the center of the positive electrode active material in the radial direction outward and the minimum distance from the center of the positive electrode active material in the radial direction outward.

[0081] As an example, the radius R of the positive electrode active material in the present application can be tested and obtained by the following method: after obtaining an electron microscope photograph of the cross-sectional structure of the positive electrode active material by scanning electron microscopy, the distance measurement module in the lithium battery material intelligent image analysis system software (software vendor: Obotong (China) Co., Ltd., version number: Metis Vision1.8326) is used to obtain it.

[0082] In some embodiments, the thickness d of the coating layer is 0-0.4R, optionally, 0-0.35R. Thus, the coating layer can effectively improve the structural stability of the positive electrode active material and has little effect on the capacity of the positive electrode active material.

[0083] As an example, the thickness d of the coating layer may be 0.05R, 0.1R, 0.15R, 0.2R, 0.25R, 0.3R, 0.35R or 0.4R.

[0084] When the thickness of the coating layer is within the aforementioned range, the thickness of the coating layer is moderate, which can not only effectively improve the structural stability of the positive electrode active material under high voltage, but also have little effect on the capacity of the positive electrode active material, and help the core, which accounts for a relatively large proportion, to fully exert its capacity.

[0085] As an example, the coating may be Figure 2 The circular area is shown by the dotted line.

[0086] As an example, refer to Figure 2 The inner boundary position of the coating layer can be determined based on the aforementioned difference in aspect ratio, and then the thickness d of the coating layer can be determined from the distance from the outer surface of the secondary particle radially inward to the inner boundary of the coating layer.

[0087] As an example, the thickness d of the coating layer in the present application can be tested by the following method: after obtaining an electron microscope photograph of the cross-sectional structure of the positive electrode active material by scanning electron microscopy, the distance measurement module in the lithium battery material intelligent image analysis system software (software vendor: Opotong (China) Co., Ltd., version number: Metis Vision 1.8326) is used to obtain it.

[0088] In some embodiments, the positive electrode active material satisfies the chemical formula: Na a (Ni 1-b-c-d Fe b Mn c M d )N e O 2-f , wherein M includes at least one of V, Ta, La, Al, Ce, Y, Ba, Zr, Ca, W, Nb, Si, Mo, F, P, and Ti, N includes at least one of Cu, Cr, Mg, Sr, Fe, Ni, Mn, Sn, Zn, B, and Co, 0.95≤a≤1.15, 0<b≤0.50, 0<c≤0.70, 0<d≤0.15, 0<e≤0.15, and f satisfies one of the following conditions: when both M and N are cations, f=0; when both M and N are anions, f=d+e; when M is an anion and N is a cation, f=d; when N is an anion and M is a cation, f=e. Thus, by doping with different elements, a positive electrode active material that meets different performance requirements can be obtained.

[0089] By doping with M elements, the structure of the transition metal layer in the layered metal oxide can be stabilized, thereby improving the structural stability of the positive electrode active material under high voltage.

[0090] By doping with N elements, a stable protective layer can be formed on the surface of the positive electrode active material, which can effectively inhibit the side reaction between the positive electrode active material and the electrolyte and improve the cycle performance.

[0091] In the second aspect of the present application, the present application proposes a method for preparing the aforementioned positive electrode active material, by adding raw materials in steps, and adopting a strategy in which the second sintering treatment temperature is slightly higher than the first sintering treatment temperature, the growth process of primary particles in the core and coating layer of the positive electrode active material is precisely controlled, so that the average particle size of the primary particles in the core is small and the aspect ratio is large, and the average particle size of the primary particles in the coating layer is large and the aspect ratio is small. The method for preparing the positive electrode active material in the present application is simple, efficient, and suitable for large-scale production. Specifically, the method includes:

[0092] S100: Mix the nickel source, iron source, manganese source, complexing agent and precipitant to obtain a precursor slurry, and dry it to obtain a precursor material.

[0093] In some embodiments, in this step, a nickel source, an iron source, a manganese source, a chelating agent and a precipitant are mixed for a co-precipitation reaction to obtain a precursor slurry, and then the precursor slurry is aged, filtered, washed and dried to obtain a precursor material.

[0094] In some embodiments, the nickel source, iron source, and manganese source each independently include at least one of sulfate, chloride, and acetate of the corresponding element. Thus, the raw material source is abundant, the environmental pollution is small, and the manufacturing cost is reduced.

[0095] In some embodiments, the complexing agent includes at least one of ammonia water, sodium oxalate, sodium citrate, and ethylenediaminetetraacetic acid. Thus, the raw material source is abundant, the environmental pollution is small, and the conventional process production line can be adapted, which helps to reduce the manufacturing cost.

[0096] In some embodiments, the precipitant includes at least one of sodium hydroxide and sodium carbonate. Thus, the raw material source is abundant, the environmental pollution is small, and the conventional process production line can be adapted, which helps to reduce the manufacturing cost.

[0097] As an example, the feed ratio of nickel source, iron source and manganese source can be calculated according to the stoichiometric ratio of the corresponding elements in the target product. The complexing agent and precipitating agent can be fed in a reasonable proportion according to the amount of nickel source, iron source and manganese source.

[0098] S200: Mix the precursor material, the sodium source, and the M source, and perform a first sintering treatment to obtain a positive electrode active material intermediate, wherein the temperature of the first sintering treatment is T1

[0099] In some embodiments, in this step, the precursor material prepared above is mixed with a sodium source and an M source, and then subjected to a first sintering treatment, as well as crushing and screening treatments to obtain a positive electrode active material intermediate.

[0100] By adding the M source as a dopant in this step, in addition to achieving uniform bulk doping and stabilizing the structure of the positive electrode active material, it also has the effect of inhibiting the continued growth of primary grains in the inner core, which helps the primary particles in the inner core to present a smaller grain size.

[0101] In some embodiments, T1 is 800° C.-960° C., and the holding time of the first sintering treatment is 10 h-15 h. This helps to form primary particles with a smaller average particle size and a larger aspect ratio in the inner core.

[0102] As an example, T1 may be 800°C, 840°C, 880°C, 920°C, or 960°C.

[0103] As an example, the holding time of the first sintering process may be 10 h, 11 h, 12 h, 13 h, 14 h or 15 h.

[0104] In some embodiments, the sodium source includes at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium sulfate, sodium chloride, sodium fluoride, and sodium sulfide.

[0105] In some embodiments, the M source includes at least one of sulfate, carbonate, oxalate, phosphate, nitrate, and chloride corresponding to the M element.

[0106] As an example, the feed ratio of the precursor material, the sodium source, and the M source can be calculated based on the stoichiometric ratio of the corresponding elements in the target product.

[0107] S300: Mixing the positive electrode active material intermediate with a N source and performing a second sintering process to obtain a positive electrode active material, wherein the temperature of the second sintering process is T2, T1<T2

[0108] In some embodiments, in this step, the positive electrode active material intermediate prepared above is mixed with a N source, and is subjected to a second sintering treatment, crushing, and sieving treatment to obtain the positive electrode active material.

[0109] During the second sintering treatment, the N source as a coating agent has the effect of promoting the growth and fusion of primary particle grains, and the N source mainly exists on the surface of the particles and has a limited content. During the second sintering treatment, it can promote the melting and growth of surface primary particles, while having little effect on the growth of primary particles in the core. As a result, the primary particles located on the surface of the particles can grow further due to the promotion effect, forming a larger primary particle coating layer with a morphology similar to that of a single crystal, and its own structure is more stable and effectively reduces the side reactions with the electrolyte, providing structural support for the circulation of positive electrode active materials at high voltage. The primary particles in the core are inhibited by the M source, and even if they still grow slowly at the temperature of the second sintering treatment, they can still maintain a small particle size. In addition, when the second sintering temperature is slightly higher than the first sintering temperature, it also helps to repair the defects of the internal grains of the positive electrode active material and further improve the performance.

[0110] In some embodiments, T2-T1<200° C.; optionally, 10° C.<T2-T1<120° C. This helps to promote the growth and fusion of primary particles in the coating layer during the second sintering process, and has little effect on the primary particles in the core.

[0111] As an example, T2-T1 may be 10°C, 30°C, 50°C, 70°C, 90°C, 110°C, 120°C, 130°C, 150°C, 170°C, 190°C, or 200°C.

[0112] In some embodiments, T2 is 850° C.-1000° C., and the second sintering treatment is performed at a holding time of 8 h-10 h. This helps to form primary particles with a larger average particle size and a smaller aspect ratio in the coating layer.

[0113] As an example, T2 may be 850°C, 900°C, 950°C, or 1000°C.

[0114] As an example, the holding time of the second sintering process may be 8 h, 8.5 h, 9 h, 9.5 h or 10 h.

[0115] In some embodiments, the N source includes at least one of oxides, sulfides, hydroxides, oxygen-containing acids, carbonates, oxalates, phosphides, and oxyhydroxides corresponding to the element N. Thus, the raw material source is abundant, the environmental pollution is small, and the manufacturing cost is reduced.

[0116] As an example, the feed ratio of the positive electrode active material intermediate to the N source can be calculated based on the stoichiometric ratio of the corresponding elements in the target product.

[0117] In the third aspect of the present application, the present application proposes a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises the aforementioned positive electrode active material or the positive electrode active material prepared by the aforementioned method. Therefore, the positive electrode sheet has all the features and advantages of the aforementioned positive electrode active material and its preparation method, which will not be described in detail here.

[0118] In a fourth aspect of the present application, the present application proposes a sodium ion battery, comprising the aforementioned positive electrode sheet. Thus, the sodium ion battery has all the features and advantages of the aforementioned positive electrode sheet, which will not be elaborated here.

[0119] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.

[0120] Example 1

[0121] A nickel source, an iron source, a manganese source, a complexing agent and a precipitant are mixed for a co-precipitation reaction to obtain a precursor slurry, and then the precursor slurry is aged, filtered, washed and dried to obtain a precursor material.

[0122] The precursor material prepared above is mixed with a sodium source and an M source, and then subjected to a first sintering treatment (sintering atmosphere is air), crushing, and sieving to obtain a positive electrode active material intermediate. The sodium source is sodium carbonate, the type of the M source, the molar ratio of the amount of each raw material, the sintering temperature, and the holding time are shown in Table 1.

[0123] The positive electrode active material intermediate prepared above is mixed with the N source, and subjected to a second sintering treatment (sintering atmosphere is air), crushing, and sieving to obtain the positive electrode active material. The type of the N source, the molar ratio of each raw material, the sintering temperature, and the holding time are shown in Table 1.

[0124] The differences between the remaining embodiments and comparative examples and embodiment 1 are shown in Table 1.

[0125]

[0126]

[0127]

[0128]

[0129]

[0130] The positive electrode active materials in the above-mentioned embodiments and comparative examples are assembled into CR2032 button batteries, and the assembly method is as follows:

[0131] The positive electrode active material, conductive agent acetylene black and binder PVDF were fully mixed in N-methylpyrrolidone at a mass ratio of 95:3:2 to form a uniform slurry, which was coated on aluminum foil and dried in an oven at 120°C for 12 hours. The positive electrode sheet with a diameter of 12 mm and a thickness of 120 mm was formed by stamping at a pressure of 100 MPa, wherein the loading amount of the positive electrode active material was 15 mg / cm 2 .

[0132] In an argon-filled glove box, the aforementioned positive electrode sheet, separator, negative electrode sheet and electrolyte were assembled into a CR2032 button cell. The negative electrode sheet used a metal sodium sheet; the separator used a polypropylene film; the solvent of the electrolyte was an equal volume mixture of ethylene carbonate, diethyl carbonate and vinylene carbonate, the electrolyte salt in the electrolyte was NaPF6, and the concentration of NaPF6 in the electrolyte was 1 mol / L.

[0133] The button cell assembled above was tested as follows. The test results are shown in Table 3:

[0134] Capacity rate test: 25℃, 2.0V-4.1V, 0.1C cycle for 2 weeks, then cycle once at 0.2C, 0.33C, 0.5C and 1C respectively, where the 0.1C first discharge capacity is the discharge capacity of the button battery in the first cycle.

[0135] 80-cycle capacity retention rate test: After the material has undergone the above rate test, continue to perform 80-cycle charge and discharge tests at a 1C rate. Divide the discharge capacity in the last cycle by the discharge capacity in the first cycle to obtain the capacity retention rate.

[0136] Table 3 Electrochemical properties of positive electrode active materials

[0137]

[0138]

[0139] Figure 1 is a scanning electron microscope photograph of the positive electrode active material in Example 1, Figure 2 for Figure 1 Cross-sectional electron micrograph of the particles. Figure 3 is a scanning electron microscope photograph of the positive electrode active material in Comparative Example 1, Figure 4 for Figure 3 Cross-sectional electron micrograph of the particles.

[0140] The test results show that when L1 / L2>1, D2 / D1>1, the primary particles in the core 10 can exert their capacity at a good level, and the primary particles in the coating layer 20 can effectively improve the structural stability, so that the positive electrode active material has both better capacity performance and higher structural stability during the charge and discharge cycle. Under the premise of meeting the high gram capacity requirements, the problems of structural instability, easy particle rupture, and poor cycle performance of the positive electrode active material in the related art during high voltage cycling are effectively overcome, thereby improving battery performance.

[0141] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode active material, characterized in that: include: A core, wherein the aspect ratio of the primary particles in the core is L1, and the average particle size of the primary particles in the core is D1; The coating layer is located on at least a portion of the surface of the inner core, the aspect ratio of the primary particles in the coating layer is L2, the average particle size of the primary particles in the coating layer is D2, L1 / L2>1, D2 / D1>1.

2. The positive electrode active material according to claim 1, characterized in that 1.5≤L1 / L2≤4.

2.

3. The positive electrode active material according to claim 1 or 2, characterized in that: L1 is 3-5.

4. The positive electrode active material according to claim 3, characterized in that L2 is 1-3.

5. The positive electrode active material according to claim 1, characterized in that 3≤D2 / D1≤13; optionally, 4≤D2 / D1≤10.

6. The positive electrode active material according to claim 5, characterized in that D1 is 0.08μm-0.3μm.

7. The positive electrode active material according to claim 5 or 6, characterized in that: D2 is 0.6μm-1.5μm.

8. The positive electrode active material according to claim 1, characterized in that The porosity of the inner core is Q1, the porosity of the coating layer is Q2, and Q1 / Q2>1.

9. The positive electrode active material according to claim 8, characterized in that 2≤Q1 / Q2≤7; optionally, 2≤Q1 / Q2≤5.

10. The positive electrode active material according to claim 8 or 9, characterized in that: 4%≤Q1≤8%。 11. The positive electrode active material according to claim 10, characterized in that 1%≤Q2≤2.5%。 12. The positive electrode active material according to claim 1, characterized in that The radius of the positive electrode active material is R, 3 μm≤R≤7 μm.

13. The positive electrode active material according to claim 12, characterized in that: The coating layer has a thickness of 0-0.4R, optionally, 0-0.35R.

14. The positive electrode active material according to claim 1, characterized in that The positive electrode active material satisfies the chemical formula: Na a (Ni 1-b-c-d Fe b Mn c M d )N e O 2-f ,in, M includes at least one of V, Ta, La, Al, Ce, Y, Ba, Zr, Ca, W, Nb, Si, Mo, F, P, and Ti, N includes at least one of Cu, Cr, Mg, Sr, Fe, Ni, Mn, Sn, Zn, B, and Co, 0.95≤a≤1.15, 0<b≤0.50, 0<c≤0.70, 0<d≤0.15, 0<e≤0.15, and f satisfies one of the following conditions: When both M and N are cations, f = 0; When both M and N are anions, f = d + e; When M is an anion and N is a cation, f = d; When N is an anion and M is a cation, f=e.

15. A method for preparing the positive electrode active material according to any one of claims 1 to 14, characterized in that: include: Mixing a nickel source, an iron source, a manganese source, a complexing agent, and a precipitating agent to obtain a precursor slurry, and performing a drying process to obtain a precursor material; The precursor material, the sodium source and the M source are mixed and subjected to a first sintering treatment to obtain a positive electrode active material intermediate, wherein the temperature of the first sintering treatment is T1; The positive electrode active material intermediate is mixed with a N source and subjected to a second sintering treatment to obtain a positive electrode active material, wherein the temperature of the second sintering treatment is T2, T1<T2.

16. The method according to claim 15, characterized in that T2-T1<200℃; optionally, 10℃<T2-T1<120℃.

17. The method according to claim 16, characterized in that T1 is 800°C-960°C, and the holding time of the first sintering treatment is 10h-15h.

18. The method according to claim 16 or 17, characterized in that T2 is 850°C-1000°C, and the holding time of the second sintering treatment is 8h-10h.

19. The method according to claim 15, characterized in that The nickel source, iron source and manganese source independently include at least one of sulfate, chloride and acetate of the corresponding element; and / or, The complexing agent includes at least one of ammonia water, sodium oxalate, sodium citrate and ethylenediaminetetraacetic acid; and / or, The precipitant includes at least one of sodium hydroxide and sodium carbonate.

20. The method according to claim 15 or 19, characterized in that The sodium source includes at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium sulfate, sodium chloride, sodium fluoride, and sodium sulfide; and / or, The M source includes at least one of sulfate, carbonate, oxalate, phosphate, nitrate and chloride corresponding to the M element; and / or, The N source includes at least one of oxides, sulfides, hydroxides, oxygen-containing acids, carbonates, oxalates, phosphides, and oxyhydroxides corresponding to the N element.

21. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 14 or the positive electrode active material prepared by the method according to any one of claims 15 to 19.

22. A sodium ion battery, characterized in that: Including the positive electrode sheet as described in claim 21.

Citation Information

Patent Citations

  • Positive electrode active material, electrochemical device and electronic device

    CN111370681A

  • Positive electrode active material, positive electrode plate and lithium ion secondary battery

    CN112447967A

  • Composite metal oxide for lithium secondary battery comprising doping element, positive electrode active material for lithium secondary battery prepared from same, and lithium secondary battery comprising same

    CN113632263A

  • Positive electrode material and preparation method and application thereof

    CN115072802A

  • Positive electrode material precursor, preparation method thereof and positive electrode material

    CN118239528A